Study on the Insulation Performance of SF6 Gas Under Different Environmental Factors - An, Yunzhu; Yin, Kaiqiang; Huang, Tao; Hu, Yuanchao; Ma, Chenghui; Yang, Minghao; An, Bingchen; Chen, Dan (Frontiers in Physics, 2022)
During the long-term operation of electrical equipment, the insulation performance of applied SF6 gas may be affected by humidity, pressure, and temperature. In this paper, the collision cross-sections of SF6 and H2O are considered, including ionization, attachment, excitation, and elastic collision. In order to analyse the influencing factors of SF6 insulation performance, discharge parameters are computed by the Boltzmann equation under different environmental conditions, including humidity, pressure, and temperature. It is concluded that with the conditions of 0.1MPa and 300K, the critical breakdown electric field increases by 1.23kV/cm as the relative humidity increases from 0% to 80%. With the pressure increases from 0.1MPa to 0.6MPa, the critical breakdown electric field increases by 451.07kV/cm. However, temperature also has little effect on the insulation performance of SF6 gas. The conclusions of this paper have reference value for the safe and stable operation of SF6 insulated power equipment.